Polypharmacotherapy with anti-obesity drugs - case report - Jakub Gołacki; Aleksandra Marczak; Michalina Hordejuk; Klaudia Sapuła; Klaudyna Iwaszko-Sochal (Kazimierz Wielki University, 2022)
Obesity is a chronic, relapsing, multi-factorial, neurobehavioral disease, wherein an increase in body fat promotes adipose tissue dysfunction and abnormal fat mass physical forces, resulting in adverse health consequences. It is diagnosed based on body mass index and waist circumference. In case of severe obesity, bariatric surgery or pharmacotherapy is recommended. We present a case report of a 28 years old man with class III obesity (77,6 kg/m2). In order to qualify the patient for bariatric surgery, a decision to combine two anti-obesity medications has been made. This kind of obesity management is neither recommended, not contraindicated, but has shown good effects on body mass reduction. This case report should initiate the discussion about recommendations modification towards combining anti-obesity medications of different mechanisms of action.